Crystal structures and docking studies in cathepsin S of bioactive 1,3‐diphenyl‐4‐(trichloro‐λ4‐tellanyl)but‐2‐en‐1‐one derivatives - Maganhi, Stella H.; Caracelli, Ignez; Zukerman-Schpector, Julio; Cunha, Rodrigo L.O.R.; Veja-Teijido, M. A.; Tiekink, Edward R. T. * (Elsevier, 2021)
The molecular structures of three 1,3‐diphenyl‐4‐(trichloro‐lλ4‐tellanyl)but‐2‐en‐1‐one derivatives (1–3), show similar coordination geometries defined by methylene-C, three chloride and carbonyl-O atoms. In each case, the resulting CCl3O donor set defines a square-pyramid with the vacant space opposite the methylene-C atom occupied by a lone-pair of electrons. Each of the molecules dimerises in the crystal via weak intermolecular Te…Cl interactions so a distorted ψ-pentagonal-bipyramidal geometry ensues. Previous work has shown these compounds to inhibit cathepsin S to varying extents, with 2, having 2-methoxy substituents in the 2-position of rings, being particularly effective. Molecular docking calculations of cathepsin S with ligands 1'–3' (i.e. cations derived from 1–3 by removal of one of the tellurium-bound chloride atoms) showed the higher experimental second order inactivation rate of 2, compared with the other two ligands, is explained by the observation that the ligand occludes the entrance to the channel thereby blocking access to the catalytic Cys25 site and also because 2' occupies part of the crucial subsite S3 of the protein.